Antibody-Drug Conjugate Targeting c-Kit for the Treatment of Small Cell Lung Cancer - Kim, Kwang Hyeok; Kim, Jin Ock; Park, Jeong Yang; Seo, Min Duk; Park, Sang Gyu (International Journal of Molecular Sciences, 2022)
Lung cancer is the leading cause of cancer-related deaths. Small cell lung cancer (SCLC) accounts for 15–25% of all lung cancers. It exhibits a rapid doubling time and a high degree of invasiveness. Additionally, overexpression of c-Kit occurs in 70% of SCLC patients. In this study, we evaluated an antibody-drug conjugate (ADC) that targets c-Kit, which is a potential therapeutic agent for SCLC. First, we generated and characterized 4C9, a fully human antibody that targets c-Kit and specifically binds to SCLC cells expressing c-Kit with a binding affinity of KD = 5.5 × 10−9 M. Then, we developed an ADC using DM1, a microtubule inhibitor, as a payload. 4C9-DM1 efficiently induced apoptosis in SCLC with an IC50 ranging from 158 pM to 4 nM. An in vivo assay using a xenograft mouse model revealed a tumor growth inhibition (TGI) rate of 45% (3 mg/kg) and 59% (5 mg/kg) for 4C9-DM1 alone. Combination treatment with 4C9-DM1 plus carboplatin/etoposide or lurbinectedin resulted in a TGI rate greater than 90% compared with the vehicle control. Taken together, these results indicate that 4C9-DM1 is a potential therapeutic agent for SCLC treatment.
Keywords: Animals; Antibodies, Monoclonal, Humanized; Carboplatin; Cell Line, Tumor; Cell Proliferation; Etoposide; Female; Humans; Immunoconjugates; Lung Neoplasms; Maytansine; Mice; Proto-Oncogene Proteins c-kit; Receptor Protein-Tyrosine Kinases; Receptor, ErbB-2; Small Cell Lung Carcinoma; Trastuzumab; Tubulin Modulators; Xenograft Model Antitumor Assays; Antibody-drug conjugate; C-Kit; Monoclonal antibody; Small cell lung cancer